Ovipositional preference of potato tuber moth and its damage to different genotypes of potato in free choice condition - Aryal, Sunil; Simkhada, Resona (Journal of Agriculture and Natural Resources, 2020)
Potato tuber moth is a serious pests of potato which cause qualitative as well as quantitative loss on tubers at stores. Major control mechanism is to use chemical pesticide but this pose great hazard risk to the growers and consumers. Therefore this study evaluated tubers of ten potato genotypes viz. CIP 394600.52, CIP 393371.164, Khumal Ujjawal, PRP 296667.2, CIP 393385.39, CIP 395112.32, PRP 226567.2, PRP 0165667.6, CIP 393371.159, and Khumal Upahar against potato tuber moths for their ovipositional preferences and damage potential with nine replication in the laboratory. Number of deposited eggs for four days at eye and outside the tubers on skin, number of tunnel and tunnel length was measured. Least percentage of egg laid eye was least in genotype CIP 394600.52, CIP 393371.164 and variety Khumal Ujjawal respectively. The least number of total eggs laid on eyes was on genotype CIP 394600.52 9 (2.33±1.00) followed by variety Khumal Ujjwal. Although genotype CIP 393385.39 and Khumal Ujjwal was among the most preferred (6.00±2.45) genotype for oviposition, average number of tunnels and average total tunnel length remained very low. Factors such as physical, nutritional, chemical or genetical which may be involved inducing resistance mechanism thus should also be studied and verified.